Pengaruh.Harga, Promosi, dan Citra Merek terhadap Keputusan Pembelian Produk Blush On Emina di Yogyakarta - Fifi Uswatun Hasanah Dema; Nur Rokhman (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2020)
Competition.between the personal. care and cosmetics industry. markets is increasingly competitive. This is. evidenced by the many types of cosmetics in circulation both domestic and. foreign production.. The flood of cosmetic products on the market influences one’s attitude towards purchasing decisions and the use of goods. Purchase a product is no longer to meet the needs (needs), but because of the desire (want). Coupled with the discovery of consumers deciding to choose to use certain products (cosmetics) in order to clarify their identity so that it is seen well in certain communities. The research method uses quantitative methods .with sampling.techniques using. nonprobability. purposive sampling., sample size is 100. Using multiple .linear regression. .analysis and the. coefficient of .determination at. a significant level of.5%. Data collection techniques using questionnaire techniques. The .results showed that. price, .promotion., and. brand image variabels had.a significant positive effect on purchasing decisions. The magnitude .of the effect of. price, promotion, and brand image on purchasing decisions 79.9% and the.remaining 20.1%..is influenced. by other. variabels not.included in.This. study.